Pengaruh Penerimaan Pajak dan Bea Balik Nama Kendaraan Bermotor terhadap Pendapatan Asli Daerah setelah Penerapan E-Samsat - Rizal Sukma Aliyudin; Eva Fauziah Ahmad; Rizka Azalia Maknunah (Department of Public Administration, 2022)
Local Own-source Revenue is income obtained by the region which is collected based on regional regulations under statutory regulations originating from various sources located in the area consisting of regional taxes, regional levies, separated regional wealth management, and other legitimate income. Local Own-source Revenue of Majalengka Regency is still not stable, as seen from the receipt of motor vehicle taxes and transfer fees for motorized vehicles which have fluctuated in realization. Therefore, this study aims to determine the effect of motor vehicle taxes and transfer fees for motorized vehicles on local own-source revenue after the implementation of e-samsat in Majalengka Regency. The research approach used in this research is descriptive analysis and verification using secondary data. The population in this study is the Realization of Regional Original Revenue Reports, especially motor vehicle taxes and transfer fees for motorized vehicles in Majalengka Regency for the 2018-2020 period. While the sample in this study was determined using the census sampling method or saturated sampling so 36 samples were obtained from January 2018 - December 2020. The analytical method used in this study was a multiple linear regression analysis carried out with the help of SPSS 25 software. Based on the research that has been done, it is obtained that the motor vehicle tax has a positive effect on local own-source revenue of Majalengka Regency and the return duty for motorized vehicles has a negative effect on the local own-source revenue of Majalengka Regency.